Radiology Jeopardy/Blank Jeopardy Template - Petra Lewis; Nancy McNulty (Association of American Medical Colleges, 2010)
Abstract This resources features a hyperlinked PowerPoint Jeopardy-style game suitable for teaching fourth-year medical students key radiological findings. Also included is a blank version of the PowerPoint for educators to make their own version on any topic. This resource is used as an interactive means of education to reinforce topics covered during a clerkship or elective. By engaging students in a game, learning is enhanced. The supplied radiology version is applicable to fourth-year medical students as well as medical interns and junior medical/surgical residents. This resource has been used in various versions for fourth-year elective students since 2003. This session has been rated as "good or excellent" by 96% of student participants. A version is given annually to radiology residents by the body imaging fellows; it has been positively received, but we do not formally evaluate that session. An important part of the learning process is taking the time to discuss the answers before moving onto the next question.